A Daoist way of being: clarity and stillness as embodied practice*. Issue 1 (2nd January 2019) - Komjathy, Louis
ABSTRACT: Daoism, especially classical Daoism, is often constructed as a 'philosophy, ' 'set of ideas, ' or 'system of thought.' This is particularly the case in studies of Chinese philosophy and comparative philosophy. The present article draws attention to the central importance of clarity and stillness ( qingjing 清靜) as a Daoist form of meditative practice, contemplative experience, and way of being. Examining historical precedents in classical Daoism, the article gives particular attention to the Tang dynasty (618–907) 'Clarity-and-Stillness Literature, ' specifically the eighth-century Qingjing jing 清靜經 (Scripture on Clarity and Stillness; DZ 620). In the process, one finds that qingjing is one of the major connective strands throughout the Daoist tradition, a connective strand that reveals the central importance of embodied, experiential, and applied dimensions of human being from a Daoist perspective.